Pharmacological methods for blood stabilization in the extracorporeal circuit (review of literature) - M. S. Mendibaev; S. E. Rabotinsky (Вестник анестезиологии и реаниматологии)
We summarize the possible benefits and risks of using various anticoagulants during hemoperfusion. Clotting in the extracorporeal circuit can lead to a decrease in the effectiveness of therapy,  additional workload,  risk to the patient and economic losses. At the same time, relatively excessive anticoagulation against the background of existing hemostasis  disorders  can lead to severe hemorrhagic complications, which in turn  worsen the prognosis of patients. The article describes the causes of heparin resistance, the main techniques for overcoming it, and provides practical guidelines for anticoagulant therapy during hemoperfusion. It is well known that routine methods of monitoring hemostasis (such as platelet count, activated partial thromboplastin time) are unable to assess the balance of pro/anticoagulants. The authors have proposed a reasonable personalized approach to anticoagulant therapy  of extracorporeal blood purification depending  on the pathology  in patient and thromboelastography (TEG) data, and antithrombin III levels.